Desempenho de genótipos de arroz com grãos especiais em diferentes densidades de semeadura em várzea de Roraima - Sá, Alex Ricarte Linhares de (2014)
The development of rice cultivars with special types of grains, such of catetos grains, aromatic, red , black , and arboreal japonica good quality and adapted to growing conditions in Brazil , constitutes a great opportunity with a view to add value the production of rice irrigation . However, these types of rice are being grown in densities based on general recommendation that may not always reflect the genetic potential of the material, in addition to the cost factor of the seed. In this context, the objective of this work was to determine the densities of seeding rice genotypes with special grains which show good adaptability to conditions in irrigated lowland of Roraima. Two experiments originated from the rice breeding program of Embrapa Roraima, designated as assays Value for Cultivation and Use (VCU) in the floodplains of the Rio Branco, in the municipality of Cantá were conducted in the period from November to March of the agricultural year the 2011/2012 and 2012/2013 in dystrophic Gleissolo Háplico tb . The delimitation was a randomized block, in design a factorial 14x4 with four replications. The treatments consisted of combinations of 12 rice genotypes with special grains and two cultivars of common rice grains with four sowing densities of 50 seeds m - 1 (60 kg ha - 1) ; 100 seeds m-1 (120 kg ha- 1); 150 seeds m-1 (180 kg ha -1), 200 seeds m-1 (240 kg ha- 1). The following characteristics were evaluated : average flowering , medium plant height ; bedding plants ; number of panicles by m2 ; number of grains by panicle ; panicle length , 1000 grain weight , number of grains by panicle , grain yield and yield of paddy rice after milling whole . The results show strong influence of planting density on most of the traits evaluated, generating a reduction in plant height , panicle length smaller and smaller number of grains per panicle with increasing seeding rate . As well as increases in the number of panicles by m2 and grain yield up to approximately 150 seeds per meter for most genotypes. Only the 1000 grain shows up slightly altered with increasing seeding rate. The Jasmine (aromatic) and RR 9903, (japonica) genotypes had the highest grain yields in the range 7000-8000 kg ha - 1 and are the most promising for use in Roraima in culture conditions in floodplain irrigation.